1983
DOI: 10.1002/micr.1920040310
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic tremor and microsurgery

Abstract: Physiologic tremor hampers the ability of students to learn microsurgical technique. An understanding of normal tremor both as to origin and methods of control would be of help. Physiological tremor arises from both mechanical and neuromuscular sources and is made worse by a number of factors. The "size principle of motoneuron recruitment" is an important physiologic consideration, and the use of biofeedback techniques enables the student to confirm his understanding of the principle. Knowledge of the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
1
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 35 publications
0
67
1
1
Order By: Relevance
“…Human hand movement has certain inherent involuntary components, including physiological tremor [1], jerk [2], and low frequency drift [3]. Suppression of these components would improve existing microsurgical practice and possibly allow the development of new procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Human hand movement has certain inherent involuntary components, including physiological tremor [1], jerk [2], and low frequency drift [3]. Suppression of these components would improve existing microsurgical practice and possibly allow the development of new procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The most obstructive problem is the physiological tremor which expands up to 0.4-0.6 mm even in the case of, well skilled microsurgeons us well 3,4,5,6 (Figure 1). Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Human hand movement contains various involuntary components, including physiological tremor [1], jerk [2], and drift [3]. These components have limited performance in microsurgery, and cause certain types of procedures to be generally infeasible, such as retinal vein cannulation and arteriovenous sheathotomy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several one-dimensional (1-D) studies of motion have been reported for microsurgeons [1,7] and medical students [8]. Some studies have examined only physiological tremor [1,8], the roughly sinusoidal component of involuntary motion.…”
Section: Introductionmentioning
confidence: 99%